CHO Cell Line Development and Engineering via Site-specific Integration: Challenges and Opportunities - Shin, Sung Wook; Lee, Jae Seong (Biotechnology and Bioprocess Engineering, 2020)
Chinese hamster ovary (CHO) cells are utilized as primary mammalian expression host cells for the production of biopharmaceuticals. Recombinant CHO cell line development (CLD) has been a crucial step for therapeutic protein production platforms; however, this step remains time-consuming and costly. With the emergence of multiomics data sets of CHO cells and genome editing technology such as CRISPR/Cas9, site-specific integration-based cell line development, and engineering have been successfully implemented in CHO cells for predictable transgene expression and expediting the process of CLD. This review describes the trends in CHO CLD from random to targeted approaches. And we cover the major obstacles faced in rational CHO CLD and the potential strategies employed to overcome its limitations. Finally, we conclude by discussing future directions and challenges for next-generation CHO cell factories.
Keywords: Biopharmaceuticals; Cell lines; Chinese Hamster ovary cells; Editing technology; Host cells; Site-specific; Therapeutic protein; Transgene expression; cell line development; Chinese hamster ovary (CHO); CRISPR/Cas9; targeted integration